Pemberdayaan “Remaja Anti Anemia” dalam Pencegahan Anemia Berbasis Pemanfaatan Pangan Lokal di SMAS Adhyaksa 1 - Nurita, Suci Rahmani; Julaecha, Julaecha; Nurfitriani, Nurfitriani; Perwitasari, Tuhu; Nurbaiti, Nurbaiti (Jurnal Abdimas Kesehatan (JAK), 2025)
The prevalence of anemia in adolescent girls is increasing, so other efforts are needed for prevention. One of the factors that influence the occurrence of anemia is iron deficiency. Handling anemia with food ingredients is still rarely done even though it has great potential to prevent anemia, especially in adolescent girls. Based on field observations, there are still adolescents who have signs and symptoms of anemia, education has been carried out regarding anemia but the role of adolescents in preventing anemia has not been active. The community service activity in the form of "Empowerment of Anti-Anemia Adolescents in Anemia Prevention Based on the Utilization of Local Foods at SMAS Adhyaksa 1" based on a mini workshop was carried out from March to August 2025 for students sent by PIK-R SMAS Adhyaksa 1 Jambi City. The purpose of this community service activity is to increase knowledge and change the attitudes of adolescent cadres about anemia prevention based on the utilization of local foods and the formation of anti-anemia adolescent cadres at SMAS Adhyaksa 1 Jambi City. The number of participants in the mini workshop consisted of 8 PIK-R female students for 1 day, given through lectures, simulations, discussions, questions and answers and Hb level screening on August 15, 2025. The material was delivered in the form of a simulation of early detection of signs and symptoms of anemia among peers using a checklist and a simulation of Hb level examination using a Hbmeter. In addition, it was also equipped with a pocket book "anti-anemia youth cadres" and a leaflet of recipes for making food made from moringa and patin. Before and after the mini workshop, a pretest and posttest were conducted to assess knowledge and attitudes about early detection of signs and symptoms of anemia and its prevention by utilizing local food. The PKM results showed that the average pre-test score of participants was 6.875 while the posttest results showed that the average score of participants was 9.375, there was a difference/difference of 2-3 points from the pretest and posttest results meaning that participants experienced an increase in knowledge and skills after being educated. It is necessary to optimize the role of youth cadres for local food-based anemia prevention